The Effect of Leg Press and Leg Extension Exercises on Long Passing in Football Players Citra Pratama U-15 Football School - Muhammad Harsya Fadilah Akbar; Ira Purnamasari; Fitri Rosdiana (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of leg press and leg extension training on long passing ability in Citra Pratama U-15 football athletes. The research method used is an experiment with a two-group pretest-posttest design. The research sample consisted of 20 athletes divided into two groups, each receiving leg press or leg extension training for six weeks. The instrument used was the Barrow Long Distance Kick Test to measure long passing ability before and after treatment. Data analysis was carried out using the Shapiro-Wilk normality test, Levene’s homogeneity test, paired t-test, and independent t-test with a significance level of 5%. The results showed: (1) Leg press training had a significant effect on increasing long passing (sig. 0.000), with an average increase of 32%. (2) Leg extension training also had a significant effect on long passing (sig. 0.000), with an average increase of 37%. (3) There was a significant difference in effect between the two exercises (sig. 0.007), where leg extension training provided a greater increase than leg press. In conclusion, both types of training are effective in improving long passing ability, but leg extension is superior in providing increased distance and shooting accuracy in U-15 football athletes.